PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN BERBASIS WAYGROUND TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SD NEGERI 139 PALEMBANG - Affriani, Dina; Puspita, Yenny; Rosmiyati, Evi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this research is based on the low Indonesian language learning outcomes of students, which are caused by the use of conventional learning methods and the still limited use of digital learning media. This study aims to find out and describe the effect of using Wayground-based learning videos on the Indonesian language learning outcomes of fifth-grade students at SD Negeri 139 Palembang. This research uses a quantitative method with a pre-experimental type and a One-Group Pretest-Posttest Design. The research sample consisted of 25 students from class VA. The data collection techniques used in this study were tests and documentation. The results showed that the average pretest score of 54.45 increased to 82.67 in the posttest. The hypothesis test using a paired sample t-test showed a significance value (Sig. 1-tailed) of 0.000 < 0.025, which means H₀ is rejected and Hₐ is accepted, so, it can be concluded that there is an effect of using Wayground-based learning videos on the Indonesian language learning outcomes of fifth graders at SD Negeri 139 Palembang.